PERANCANGAN TATA LETAK PADA PRODUKSI TEPUNG - Jihan Fadhilah Lukman; Unggul Timotius, Hendra Johanes Hutauruk, Danang Novianto, Slamet Nugraha (ADISAM PUBLISHER, 2026)
Wheat flour is flour obtained from milled wheat grains. Wheat grains consist of three parts, namely skin, endosperm, and embryo. The skin and embryo are parts that are not consumed, while the endosperm is the part that will become wheat flour. The main purpose of planning the layout of facilities that will aflect flour production is to increase efficiency, reduce production costs and improve the products to be made. In various production companies, safety and ergonomic aspects are very important in order to protect the company's employees. In this way, we do not directly create a safe and peaceful working atmosphere. Occupational safety is something that must be done so that employees are safe and there are various methods in flour production, namely the Activity Template Block Diagram, Activity Relationship Diagram and AreaAllocation Diagram